2021
DOI: 10.3389/fpsyg.2021.588767
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being in Obstructive Sleep Apnea Syndrome Associated With Obesity: The Relationship With Personality, Cognitive Functioning, and Subjective and Objective Sleep Quality

Abstract: Obstructive sleep apnea (OSA) syndrome severely affects psychological well-being. This syndrome frequently occurs in obesity; however, no previous study has investigated the level of psychological well-being in the case of OSA syndrome associated with obesity. In this work, we assessed the level of psychological well-being in fifty-two individuals affected by OSA syndrome and obesity through the Psychological General Well-Being Index. Moreover, we investigated the role of personality, cognitive functioning and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
5
11
0
Order By: Relevance
“…Some final considerations can be done about our study. The first one regards the scores registered at the temperament and Character Inventory-Revised (Martinotti et al, 2008), according to which our participants showed higher expressions of novelty seeking temperamental trait in comparison with the normative data (Martinotti et al, 2008), in agreement with recently published results provided by our group (Scarpina et al, 2021). We also reported that our participants showed higher expressions of the persistent temperamental trait.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Some final considerations can be done about our study. The first one regards the scores registered at the temperament and Character Inventory-Revised (Martinotti et al, 2008), according to which our participants showed higher expressions of novelty seeking temperamental trait in comparison with the normative data (Martinotti et al, 2008), in agreement with recently published results provided by our group (Scarpina et al, 2021). We also reported that our participants showed higher expressions of the persistent temperamental trait.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the interaction Condition × Time was not significant [F (3, 126) = 1.38; p = 0.25; partial etasquared p = 0.03] (Figure 2D). This pattern of results suggested that the performance of our participants was in agreement with the Flanker's effect, mirroring the results reported by Scarpina et al (2021). Crucially, after the rehabilitation, participants were faster in detecting the visual targets, suggesting an improvement of their attentional abilities.…”
Section: Secondary Outcomessupporting
confidence: 90%
See 2 more Smart Citations
“…Adherence to CPAP use might, therefore, depends on factors other than disease-specific characteristics or technological advancements in the delivery of positive airway pressure, including psychological, motivational, and environmental aspects. These encompass characteristics of negative affectivity and social inhibition associated with Type-D (distressed) personality (Broström et al, 2007 ; Copur et al, 2018 ), or symptoms of claustrophobia (Chasens et al, 2005 ), while research findings are inconclusive on the association between mood disorders, such as anxiety and depression, and adherence to CPAP (Stepnowsky et al, 2002 ; Garbarino et al, 2018 ; Yang et al, 2020 ; Scarpina et al, 2021 ). Additional factors include coping styles with challenging situations (active vs. passive), treatment expectations, and perceived self-efficacy (i.e., confidence in one's own ability to carry out a particular behavior) (Aloia et al, 2005 ; Olsen et al, 2008 ; Baron et al, 2011 ; Sawyer et al, 2011 ; Mehrtash et al, 2019 ), together with social support (Lewis et al, 2004 ; Xu et al, 2020 ), and marital satisfaction (i.e., problems with the bed partner) (Batool-Anwar et al, 2017 ; Luyster, 2017 ; Gentina et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%